Balancing nutrition for successful reproduction in ruminants - Yitong Ding; Xinyue Liu; Yueming Guan; Zimu Li; Mengcheng Luo; Duanqin Wu; Lan Ye; Liu Guo; Leli Wang; Yongjuan Guan (Modern Agriculture)
Abstract Proper nutrition is essential for sustaining optimal reproductive function in both humans and ruminants. Studies have shown that both undernutrition and overnutrition can negatively impact human reproductive processes. However, the Mediterranean diet, with its balanced and nutrient‐rich composition, is recognised for its positive effects on human reproduction. In the context of ruminants, a well‐balanced and nutrient‐rich diet is equally crucial for achieving peak reproductive performance. Grazing, which allows ruminants to feed on natural pasture in open environments, contrasts with indoor feeding, which is conducted in more controlled settings. A balanced dietary approach is vital for the successful reproduction of ruminant animals, and a combination of grazing and indoor feeding has been identified as an effective strategy to enhance their reproductive success. This review emphasises the impact of nutrition on reproductive outcomes in both human and ruminant populations, advocating for balanced dietary practices to improve reproductive success across species. A thorough understanding of the complex relationship between nutrition and reproductive health can offer valuable insights into enhancing fertility and reproductive efficiency in various contexts.